Experimental investigation on the tensile, flexural, and thermal rigidity of ALON-reinforced Kevlar fabric-impregnated epoxy composites - Chenrayan V.; Shahapurkar K.; Muthusamy S.C.; Shanmugam S.K.; Zewdu G.A.; Arunachalam A.; Soudagar M.E.M.; Fouad Y.; Murthy H.C.A. (Springer Science and Business Media Deutschland GmbH, 2025)
Increasing demand for high-performance lightweight materials for structural applications poses a challenge to material research and development; subsequently, the expectation of a single lightweight material to sustain itself in a multi-functional environment is also difficult. The present research attempts to address the above-said issue by developing and examining the structural stability of aluminum oxynitride (ALON)-reinforced Kevlar fabric-impregnated epoxy composite. Three different weight percentages 5, 10, and 15 of ALON particles are employed to fabricate the composite sheet through the hand-layup technique. The novel inclusion of ALON particles in the resin-impregnated composite is expected to improve its structural stability. Tensile, flexural, and dynamic mechanical tests are conducted to assess the improved structural stability conforming to standards. The results comprehend the significant improvement of 1.75 times in tensile, 2.59 times in flexural, and 1.28 times in damping characteristics for the higher composition of ALON particles compared to the ALON-free composite. The collective outcome of the study delineates that the novel composite is the right candidate for structural loading. The fracture study conducted through a scanning electron microscope reveals that the failure propagation is followed by collective delamination. ? The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.